2002
DOI: 10.1038/sj.cdd.4401010
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of nuclear matrix proteins during apoptotic chromatin condensation

Abstract: The nuclear matrix (NM) is considered a proteinaceous scaffold spatially organizing the interphase nucleus, the integrity of which is affected during apoptosis. Caspasemediated degradation of NM proteins, such as nuclear lamins, precedes apoptotic chromatin condensation (ACC). Nevertheless, other NM proteins remain unaffected, which most likely maintain a remaining nuclear structure devoid of chromatin. We, therefore, screened various types of apoptotic cells for changes of the nuclear matrix proteome during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 71 publications
3
54
0
Order By: Relevance
“…One of the classes of proteins in this study includes nuclear membrane, nuclear pore, and structural proteins. Our results support earlier findings that suggested involvement of lamins, nuclear envelope proteins, actins, and myosin in the core nucleoskeleton (16). In addition to these core nucleoskeleton proteins, we identified a number of novel structural proteins involved in actin and microtubule binding as NuMat components.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…One of the classes of proteins in this study includes nuclear membrane, nuclear pore, and structural proteins. Our results support earlier findings that suggested involvement of lamins, nuclear envelope proteins, actins, and myosin in the core nucleoskeleton (16). In addition to these core nucleoskeleton proteins, we identified a number of novel structural proteins involved in actin and microtubule binding as NuMat components.…”
Section: Discussionsupporting
confidence: 80%
“…This diversity among the small number of identified NuMat constituents reflects the link of nuclear architecture with the variety of nuclear functions. The importance of NuMat constituents in nuclear processes has been apparent for a long time, and several studies have been carried out to identify the proteins of this complex structure in different organisms (15)(16)(17)(18). Major advancements in the field of proteomics now provide further scope for extensive analysis of NuMat in this context.…”
mentioning
confidence: 99%
“…14-3-3 epsilon is cleaved by caspase during apoptosis (Nomura et al 2003), which explains the observed reduction of full length 14-3-3 proteins in prolonged CHO culture. Meanwhile, cleavage of LAMR1, which forms the structural component of ribosomes, has been reported in apoptotic cells and proposed to have a pro-apoptotic effect (Gerner et al 2002). Galectins are beta-galactoside-binding proteins that regulate various cellular activities including differentiation, apoptosis, cell growth, and tumor progression (Carlage et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing list of nuclear protein which are degraded during apoptosis (Fischer et al, 2003), although for several among them the precise role of a single protease has not yet been elucidated; chromatin collapse and alteration of the nuclear envelope are likely the consequence of the proteolytic cleavage of proteins such as lamins (Rao et al, 1996;Gerner et al, 2002), emerin (Columbaro et al, 2001), pore components (Nup 153, Nup 214, Tpr: Ferrando-May et al, 2001), Acinus (Sahara et al, 1999) and NuMa (Hsu and Yeh, 1996).…”
Section: Degradation Of Chromatin and Chromatin-associated Componentsmentioning
confidence: 99%
“…These calcium-dependent proteases are present in the cell in inactivated forms, and their activation requires proteolytic cleavage taking place in a cascade-like process (Donepudi and Grutter, 2002;Shi, 2002): the so-called initiator caspases act on effector caspases which finally cleave a wide spectrum of cytoplasmic and nuclear structural substrates. It is worth recalling that apoptotic events may occur even in the absence of activated caspases, as it occurs in avian sperm and erithrocytes (Weil et al, 1998).There is a growing list of nuclear protein which are degraded during apoptosis (Fischer et al, 2003), although for several among them the precise role of a single protease has not yet been elucidated; chromatin collapse and alteration of the nuclear envelope are likely the consequence of the proteolytic cleavage of proteins such as lamins (Rao et al, 1996;Gerner et al, 2002), emerin (Columbaro et al, 2001), pore components (Nup 153, Nup 214, Tpr: Ferrando-May et al, 2001), Acinus (Sahara et al, 1999) and NuMa (Hsu and Yeh, 1996).Nuclear proteins may be also modified post-translationally, during apoptosis: besides the widely investigated process of poly (ADP-ribosyl)ation (for a recent review, see Soldani and Scovassi, 2002), in particular hyperphosphorylation occurs in lamins (Shimizu et al, 1998), histones (H3: Waring et al, 1997 H2B and H4: Ajiro, 2000; and H2AX: Rogakou et al, 2000) and HMGA1 protein (Diana et al, 2001). In general, these changes have been interpreted as an adaptive process, which increases the susceptibility of nuclear components to disruption and/or disassembly (Martelli et al, 2001).…”
mentioning
confidence: 99%